Impact of e-Services on Customer Satisfaction: A B2B Physical Distribution Service Quality Perspective - KARPUZCU, TUGCE (2010)
E-commerce has provided companies almost in every industry to introduce new ways of serving their customers. As with any other markets, physical distribution service (PDS) industry experienced an upswing in the adoption of e-services by companies, and consequently their business customers. A great deal of factors exist for impeding or enhancing the adoption of e-commerce by B2B customers. With the increased number of benefits provided by conducting e-commerce, companies have been facing challenges in making the customers adopt and use e-services. One way of achieving this is providing high quality e-services and consequently achieving customer satisfaction, which received extensive academic attention in the service quality literature, although not specifically in business-to-business PDS industries. Various tools have been developed for measuring e-service quality in online PDS markets, such as Internet retailers. However, not much academic emphasis was put on total service quality in multi-channel physical distributors, such as industrial wholesaler/distributors having alternative electronic channels. This study attempted to develop two instruments for measuring physical distribution and e-service quality separately in multi-channel non-retail PDS industries by emphasizing different channel preferences of B2B customers with respect to their underlying reasons. The instruments are exercised with a single questionnaire by a sample of customers belonging to the focus company in the industry in question, and several results are obtained. The dimensions that determine the level of service quality in physical distribution and electronic services, separately, for the business context were found by detailed analysis of relevant literature. Results revealed that all PDS quality dimensions have significant impact on customers’ overall satisfaction from the distributor’s services, and all e-service quality determinants have significant impact on customers’ e-satisfaction, while some of these were also found to impact the overall satisfaction significantly. It was found that some of these impacts are moderated by customer characteristics, such as the age of relationship with the distributor, and the amounts regularly purchased from it. Given that customers differ in terms of the level of their involvement in the e-services and the amount of e-commerce activities they engage in, significant differences were found between their evaluations of the distributor’s e-service quality, while no difference existed between their perceptions of PDS quality. This study provides valuable insights for the multi-channel non-retail PDS industries in terms of the reasons underlying customers’ channel preferences and the aspects vital for achieving total quality in their services and respective customer satisfaction.